Poverty, Lack Of Awareness Of Gender Education, And Patriarchy Among Javanese Coastal Women - Sudarso, Sudarso; Edy Keban, Phillipus; Mas’udah, Siti (Opción, 2019)
This study aims to examine the poverty, awareness of gender education, and patriarchal culture in Javanese coastal-dwellers. The study applied a quali- tative approach by interviewing 70 informants. The results showed that ed- ucation for coastal-dwellers was not recognized as an important aspect. In addition, they believed that the wheels of the economy were running because of the role of men ignoring the role of women in marine and fisheries econom- ic activities. They were also married at a young age because of their insuffi- cient awareness and understanding, thus these women could not escape from poverty and their cultural shackles. These women need to be empowered, at least in order to give them enough skills to manage their maritime potential. In addition, they deserve a better education so that they can escape from the poverty zone.